2005
DOI: 10.1128/mcb.25.11.4591-4601.2005
|View full text |Cite
|
Sign up to set email alerts
|

Bim Regulation of Lumen Formation in Cultured Mammary Epithelial Acini Is Targeted by Oncogenes

Abstract: Epithelial cells organize into cyst-like structures that contain a spherical monolayer of cells that enclose a central lumen. Using a three-dimensional basement membrane culture model in which mammary epithelial cells form hollow, acinus-like structures, we previously demonstrated that lumen formation is achieved, in part, through apoptosis of centrally localized cells. We demonstrate that the proapoptotic protein Bim may selectively trigger apoptosis of the centrally localized acinar cells, leading to tempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
177
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(191 citation statements)
references
References 38 publications
11
177
2
1
Order By: Relevance
“…Due to the fact that ERK-mediated protection from anoikis in other cell lines has previously been shown to involve targeting of the pro-apoptotic protein Bim-EL for degradation, 23 we investigated the protein levels of Bim-EL in IBC cells that have been treated with increasing doses of U0126. Much to our surprise, we found that, contrary to published reports in other cell types, inhibition of the ERK pathway did not result in dramatically increased levels of Bim-EL.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the fact that ERK-mediated protection from anoikis in other cell lines has previously been shown to involve targeting of the pro-apoptotic protein Bim-EL for degradation, 23 we investigated the protein levels of Bim-EL in IBC cells that have been treated with increasing doses of U0126. Much to our surprise, we found that, contrary to published reports in other cell types, inhibition of the ERK pathway did not result in dramatically increased levels of Bim-EL.…”
Section: Resultsmentioning
confidence: 99%
“…[18][19][20] Interestingly, previous studies have shown that ErbB2 and EGFR, which are hyperactivated in a substantial percentage of IBC patients, 21 can effectively antagonize the anoikis program to facilitate anchorage-independent growth. [22][23][24][25][26][27][28] However, a detailed examination of the molecular mechanisms underlying anoikis inhibition in IBC cells has yet to be completed. In this study, we demonstrate that signaling from EGFR and ErbB2 through ERK/MAPK has a major role in the ability of IBC cells to survive in the absence of ECM attachment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Enhanced phosphorylation of BIM EL in BAG-1-expressing acini BIM is a critical effector of luminal cell death in MCF-10A acini (Reginato et al, 2005). Its expression is regulated by ERK-mediated phosphorylation on serine 69 (S69), which subsequently targets it for proteasomal degradation (Ley et al, 2003;Luciano et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…This phenotype typifies those seen in most breast carcinomas and preinvasive lesions such as ductal carcinoma in situ, as well as some precancerous states such as atypical ductal hyperplasia (Harris et al, 1999), suggesting that disruption of the normal apoptotic program may have an important role in the initiation and progression of breast cancer. Studies aimed at elucidating the molecular mechanisms governing the formation and maintenance of the luminal space have demonstrated that it may be influenced both by Akt-mediated survival signals in the matrix-associated outer cells (Debnath et al, 2002) and active, BIMmediated apoptotic signals in the centrally localized cells (Reginato et al, 2005;Mailleux et al, 2007). BIM is upregulated immediately before the initiation of apoptosis and is specifically inhibited by prosurvival oncoproteins through stimulation of MEK-ERK signaling (Reginato et al, 2005).…”
Section: Discussionmentioning
confidence: 99%